Pengaruh Motivasi, Pengetahuan Mata Kuliah Perpajakan, dan Literasi Perpajakan Terhadap Minat Mahasiswa dalam Berkarir di Bidang Perpajakan (Studi Kasus Mahasiswa di Kota Malang) - Irfandi, Hanif; Malikah, Anik; Mawardi, M. Cholid (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research aims to determine the influence of motivation, knowledge of tax subjects and tax literacy on students' interest in pursuing a career in taxation. This research uses study data on Bachelor of Accounting student class of 2020 at the Islamic University of Malang, Maulana Malik Ibrahim State Islamic University of Malang and Muhammadiyah University of Malang who participated in this quantitative survey. Data collection in this study used a questionnaire using Google Form with a 1-5 Likert scale. Determining the sample size used the Slovin formula and the results obtained were 240 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results of research tests prove that motivation, knowledge of tax subjects and tax literacy have a positive and significant effect on students' interest in pursuing a career in taxation.Keywords: Motivation, knowledge of tax subjects, tax literacy, student interest in a career in taxation.